Benefits of virtual reality in the treatment of patients with Parkinson's disease: literature review - Brito, Sara Ferreira Lobato de (2022)
Introduction: Parkinson’a disease (PD) is a neurodegenerative disease of the central nervous system, with a chronic and progressive character, the diagnosis of PD is clinical, having as main characteristic the combination of motor symptoms that include bradykinesia, rigidity, tremor and postural instability. Objectives: The objective of is study was to review literature data on the benefits of virtual reality treatment in PD. Methodology: This is qualitative literature review, carried out between January and April 2022, using original articles, case studies and experience reports, published in journals indexed in online databases. Line: Virtual Health Library (VHL), Pubmed and SciELO. Results: The analyzed Studies found varied results regarding the use of virtual reality assistive technologies(ART) and its benefits in the treatment of PD, which were related to topics such as prospective memory, brain activation and, more frequently, gait and balance training. Thus, the most significant results regarding the use of ART were related to gait and balance training. Conclusion: The use of ART can bring benefits in the treatment of Parkinson’s disease as it has shown significant results in gait training, improving balance and reducing the risk of falls.